Exercise Based Intervention for Dysmenorrhea: The Role of Abdominal Stretching and William’s Flexion - Refti, Weni Guslia; Primasari, Sefria Indah; Irayani, Fahrul (Jurnal Ilmiah STIKES Yarsi Mataram, 2026)
Adolescence is a critical phase of human development characterized by rapid physical, psychological, and cognitive changes. One of the common reproductive health problems experienced by adolescent girls is primary dysmenorrhea, which is menstrual pain caused by excessive uterine contractions and increased prostaglandin levels. This condition can disrupt daily activities, learning concentration, and overall quality of life. This study aimed to analyze the effects of Abdominal Stretching Exercise and William’s Flexion Exercise on the intensity of menstrual pain among ninth-grade female students at SMP Dharma Bhakti Waypanji, Kalianda, South Lampung. The study employed a quasi-experimental pre–post test design with two intervention groups. The sample consisted of 48 ninth-grade students with primary dysmenorrhea, selected using total sampling. The first group received Abdominal Stretching Exercise, while the second group received William’s Flexion Exercise, each performed for 10–15 minutes per session under supervision to ensure proper execution. Pain intensity was measured before and after the intervention using the Numeric Rating Scale (NRS). Data were analyzed using an Independent t-test with a significance level of α = 0.05. The results showed that both interventions significantly reduced menstrual pain. The mean pain score in the Abdominal Stretching group decreased from 2.79 to 2.58 (p = 0.022), while the William’s Flexion group showed a greater reduction, from 2.79 to 1.54 (p = 0.000). The Independent t-test confirmed a significant difference in post-intervention pain scores (t = 5.802; p = 0.000), with William’s Flexion Exercise being more effective. These findings support the physiological theory that strengthening the abdominal and lumbar muscles, improving pelvic circulation, and promoting neuromuscular relaxation contribute to the reduction of uterine contractions and pain perception. In conclusion, William’s Flexion Exercise is more effective than Abdominal Stretching Exercise in reducing the intensity of dysmenorrhea. It is recommended that schools and health professionals incorporate this exercise as a routine non-pharmacological method for managing adolescent dysmenorrhea.